NILAI-NILAI PENDIDIKAN KARAKTER UNTUK ANAK USIA DINI DALAM FILM “NUSSA”: CHARACTER EDUCATION VALUES FOR EARLY CHILDHOOD IN THE FILM "NUSSA" - Fardani, Diah Novita; Lismanda, Yorita Febry (Thufuli, 2019)
Early Childhood has a variety of interests, one of them is the fondness of watching television shows that are animated cartoons. At an early age, children have a strong tendency to mimic everything they see. This becomes important considering that a lot of animated cartoon films are shown and are often seen by children which certainly affects the character and personality of children. This study aims to determine the values of character education for early childhood contained in the animated film "Nussa". In carrying out this study using a qualitative descriptive approach by analyzing the contents of four randomly selected episodes. The results of this study found that educational values characters for early childhood contained in the four episodes of the animated film "Nussa" are very diverse, among the character values contained such as religious, hard work, independent, friendly and communicative, honest, caring socially, creatively, disciplined, rewarding achievement, and responsibility.